Age- and sex-related differences in the anthropometry and neuromuscular fitness of competitive taekwondo athletes - Nikolaidis, P. T.; Busko, K.; Clemente, F. M.; Tasiopoulos, I.; Knechtle, B. (Open Access Journal of Sports Medicine, 2016)
Anthropometry and neuromuscular fitness have been shown to relate with taekwondo (TKD) performance; however, little information is available on the variation of these fitness components by sex and age in athletes practicing this sport. The aim of the present study was to examine the anthropometry and neuromuscular fitness of TKD athletes by sex and age. A total of 393 athletes (7-48 years old), separated into six age groups (7-9, 10-11, 12-13, 14-17, 18-32, and 33+), were examined for anthropometry and performed a series of neuromuscular fitness tests (flexibility, agility, muscle power, and isometric strength). An age × sex interaction on body mass, body height, and body fat percentage (BF, p=0.003, 2=0.045), but not on body mass index (p=0.172, 2=0.020), was shown, where a larger increase in body mass and body height from 12-13 to 14-17 groups was observed in males than in females, and the sex difference in BF increased from 12-13 to 14-17 age group. An age × sex interaction on sit-and-reach (SAR) test, mean power output in the Bosco test, and Abalakov jump (p=0.038, 2=0.031) was observed with larger differences between 12-13 and 18-32 groups in males than in females. In SAR, it was remarkable that the male athletes achieved similar scores as female athletes in the 18-32 group. An age × sex group interaction on measures of isometric muscle strength (right and left handgrip, trunk, and legs) was also shown (p=0.002, 2=0.068), where larger differences in male than female athletes were observed between the 12-13 and 14-17 groups. From a practical perspective, coaches can use these findings as reference for the evaluation of their athletes. Because the anthropometric characteristics and neuromuscular fitness varied by sex (i.e., highest scores in males, except flexibility) and age (i.e., highest scores in the 18-32 age group) with unique sport-specific patterns in TKD athletes, these findings would be important for the development of specific training programs.